Aminoalkyl‐1, 1‐bis(phosphinic acids): Stability, Acid–Base, and Coordination Properties. Issue 26 (30th July 2014) - David, Tomáš; Procházková, Soňa; Kotek, Jan; Kubíček, Vojtěch; Hermann, Petr; Lukeš, Ivan
Abstract: Four geminal bis(phosphinic acids), namely, aminomethylbis( H ‐phosphinic acid) (H2 L 1 ) and 4‐aminobutyl‐1‐hydroxy‐1, 1‐bis(R‐phosphinic acid) with R = H (H2 L 2 ), Me (H2 L 3 ) and CH2 CH2 COOH (H4 L 4 ), were studied. Their acid–base properties and coordination ability towards Cu 2+, Ni 2+ and Zn 2+ ions were studied by potentiometry, UV/Vis spectroscopy and NMR spectroscopy. The amine group in H2 L 1 has a lower protonation constant (log  K a = 6.79) than those found for other studied bisphosphinates (log  K a = 10.75–11.05) with distant amine groups. The structure of [Ca(H2 L 2 ‐ O, O′ )(HL 2 ‐ O, O′ )]Cl revealed an octahedral arrangement of the metal coordination sphere and a linear polymeric structure, which forms through eight‐membered Ca(–O–P–O–)2 Ca rings. The structure of [Cu(HL 3 ‐ O, O′ )2 (H2 O)]· 5H2 O shows two chelating bisphosphinate groups in an equatorial O4 environment. The structure of [Cu(H0.5 L 3 ‐ O, O′ )(NO3 )0.5 ]· 2.25H2 O shows two different coordination environments, one is an elongated tetragonal pyramid, and the other is a trigonal bipyramid with a bidentate nitrate ion. Abstract : Four geminal bisphosphinates were synthesized, and their acid–base properties and coordination behaviour with Cu 2+, Zn 2+ and Ni 2+ ions were studied. The compounds show lower amine basicity and complex stability constants than those of analogous bisphosphonates. In the solid‐state structures of the Ca 2+ and Cu 2+ complexes, the bisphosphinates are coordinated in O, O ′‐chelating mode.